New Cosmopolitanisms : South Asians in the U.S. - Rajan, Gita (Stanford University Press, 2005)
Offers an in-depth look at the ways in which technology, travel and globalization have altered traditional patterns of immigration for South Asians who live and work in the United States. This book explains how their popular cultural practices and aesthetic desires are fulfilled.